Peranan Guru Pendidikan Agama Kristen Dalam Meningkatkan Hasil Belajar Melalui Model Pembelajaran Gambar dan Gambar - Lumempouw, Nova Liesye; Sutrisno, Sutrisno; Hutabarat, Christiani; Soukotta, Dunant F. (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2022)
The Role of Christian education teachers in improving learning outcomes through picture and picture is one of the teaching aids for teachers to increase creativity and students in the learning process. By using the picture and picture learning model students will be more motivated, students' imaginations are stimulated, their feelings are touched, and a deep impression is obtained by students and then it influences students to want to improve. The use of picture and picture learning models can increase students' attention with new pictures. will feel happy about the subject matter, not only hear the names of Bible characters but can immediately see their pictures or photos. That is why it is very important to discuss the teaching of Christian religious education with teaching aids for elementary school students. In the teaching of Christian Religious Education, the use of learning models is not a new thing, during the Old Testament period, the use of teaching aids was still very limited. In the new covenant as a teacher, the Lord Jesus always looks for and finds various ways to deal with the situation of His listeners, namely with other models such as lectures, questions, and answers, so that they are more interesting and can be well received. In general, the existence of learning models appears so as not to be fixated on only one learning model. However, with the innovation, the picture and picture learning model are better for students to be able to remember each subject matter. Peranan guru pendidikan agama Kristen dalam meningkatkan hasil belajar melalui model pembelajaran picture and picture adalah salah satu alat bantu mengajar bagi guru untuk meningkatkan kreatifitas dan siswa dalam proses pembelajaran. Dengan menggunakan model pembelajaran picture and picture siswa akan lebih termotivasi, imajinasi siswa di rangsang, perasaannya di sentuh dan kesan yang dalam diperoleh siswa dan selanjutnya mempengaruhi siswa ingin lebih meningkatkan Penggunaan model pembelajaran picture and picture dapat meningkatkan perhatian siswa dengan gambar-gambar yang baru siswa akan merasa senang terhadap materi pelajaran, tidak hanya mendengar nama tokoh-tokoh Alkitab tapi tapi langsung bisa di lihat gambar atau foto mereka. Itu lah sebabnya, pengajaran pendidikan Agama Kristen dengan alat peraga bagi siswa sekolah dasar sangat penting di bahas. Dalam pengajaran Pendidikan Agama Kristen, pemanfaatan model pembelajaran sebenarnya bukan hal yang baru, pada masa perjanjian lama sudah memakai alat peraga sekalipun masih sangat terbatas. Dalam perjanjian baru sebagai guru, Tuhan Yesus selalu mencari dan menemukan berbagai cara dalam menghadapi situasi pendengar-Nya yaitu denan model yang lain seperti ceramah, tanya jawab, sehingga lebih menarik dan dapat di terima dengan baik. Pada umumnya keberadaan model pembelajaran muncul agar jangat terpaku pada satu model pembelajaran saja. Akan tetapi, dengan inovasi baru model pembelajaran picture and picture lebih baik untuk siswa dapat mengingat setiap materi pelajaran.